Patient Perception of Physicians and Medication Adherence Among Older Adults With Hypertension. (January 2020) - Ward, Lori M.; Thomas, Joseph
Objective: To assess association between patient perception of physicians and adherence to antihypertensive medication among Medicare beneficiaries.Method: Logistic regression was used to assess association between the Patient Perception of Physicians Scale score and adherence to antihypertensive medication. The 2007 Medicare Current Beneficiary Survey data were used to create a 12-item patient perception of physician scale and 2008 Medicare Part D claims to assess adherence.Results: There were 2, 510 beneficiaries included in the sample. The mean age was 76.4 years ( SD = ±6.88 years). Sixty-five percent of the sample was adherent in filling their antihypertensive medication. Beneficiaries with more favorable perceptions of their physician (scores 37 or higher) were more likely to be adherent to antihypertensive medications than beneficiaries with scores less than 37 (odds ratio [OR] = 1.341, 95% confidence interval [CI] = [1.101, 1.632], p = .0035).Discussion: These findings provide some evidence that patient perceptions of their physician are associated with adherence, and that the physician–patient relationship is an important factor.